To share or not to share – The underlying motives of sharing fake news amidst the COVID-19 pandemic in Malaysia. (August 2021) - Balakrishnan, Vimala; Ng, Kee S.; Rahim, Hajar Abdul
Abstract: This study investigates the underlying motives for online fake news sharing during the COVID-19 pandemic, an unprecedented time that witnessed a spike in the spread of false content. Motives were identified based on a fake news sharing model developed using the SocioCultural-Psychological-Technology (SCulPT) model, Uses and Gratification (U&G) theory and Self-Determination Theory (SDT), and further extended using fake news predictors/gratifications from past studies. A self-administered survey resulted in 869 online Malaysian respondents aged between 18 and 59 years old (Mean = 22.6, Standard deviation = 6.13). Structured equation modelling revealed the fake news sharing model to collectively account for 49.2 % of the variance, with Altruism (β = 0.333; p < 0.001), Ignorance (β = 0.165; p < 0.001) and Entertainment (β = 0.139; p < 0.001) significantly predicting the behaviour. Conversely, Availability/Effort, Pass Time and Fear of Missing Out were found to be insignificant. Our findings indicate that fake news sharing behavior is determined by different motives, hence these need to be understood in order to develop better solutions to mitigate this problem. Highlights: Study identified underlying motives for fake news sharing during COVID-19 pandemic. Six motives explain 49.2 % of fake news sharing behavior. Altruism and Ignorance had significant moderate effect on fake news sharing. Entertainment had a significant weak effect on fake news sharing. Availability/Effort, Pass Time and Fear of Missing Out were insignificant motives.